PENGARUH FASILITAS DAN PROMOSI TERHADAP KEPUASAN PENGUNJUNG KE OBJEK WISATA PEMANDIAN AIR PANAS TIRTA LEBAK BUANA DI LEBAK BANTEN Syalsya Frida Kusnadi1, Senen2 - Frida Kusnadi, Syalsya; Senen (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to examine the Influence of Facilities and Promotions on Visitor Satisfaction at the Tirta Lebak Buana Hot Spring Tourism Object, both partially and simultaneously. The study employs a quantitative approach with probability/random sampling technique, where every member of the population has an equal chance of being selected as a sample. The study includes a sample size of 99 respondents. The research findings indicate that Facilities (X1) and Promotions (X2) significantly influence Visitor Satisfaction, with a regression equation of Y = 0.536 + 0.420X1 + 0.588X2. The coefficient of correlation, indicating the strength of the relationship between the independent variables and the dependent variable, is 0.806, indicating a strong correlation. The coefficient of determination is 0.802, suggesting that Facilities and Promotions account for 80.2% of the variance in Visitor Satisfaction, while the remaining 19.8% is influenced by other factors not examined in this study. The hypothesis test results show that the computed F value (199.946) exceeds the tabulated F value (3.090), and the p-value (0.000) is less than the significance level (0.05), leading to the rejection of the null hypothesis (H0) and acceptance of the alternate hypothesis (H3). This indicates a significant simultaneous effect of Facilities and Promotions on Visitor Satisfaction at the Tirta Lebak Buana Hot Spring Tourism Object.